2010
DOI: 10.1007/s11307-010-0306-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrated PET/CT Fusion Imaging and Endoscopic Ultrasound in the Pre-operative Staging and Evaluation of Esophageal Cancer

Abstract: In ECA, EUS is superior to PET/CT for T staging and in identifying locoregional nodes, while PET/CT provides M staging. EUS and integrated PET/CT appear to independently affect treatment decisions, indicating complimentary and necessary roles in the staging of ECA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 28 publications
0
33
1
3
Order By: Relevance
“…For patients being considered for a curative pathway, endoscopic ultrasound (EUS) and 18F-fluorodeoxyglu-cose positron emission tomography/CT (18F-FDG PET/ CT) are performed due to the high sensitivity and specificity of EUS for local tumor and nodal staging; and 18F-FDG PET for distant metastases [17][18][19]. This aims to reduce the futile surgery rate.…”
Section: The Imaging Pathway At Stagingmentioning
confidence: 99%
“…For patients being considered for a curative pathway, endoscopic ultrasound (EUS) and 18F-fluorodeoxyglu-cose positron emission tomography/CT (18F-FDG PET/ CT) are performed due to the high sensitivity and specificity of EUS for local tumor and nodal staging; and 18F-FDG PET for distant metastases [17][18][19]. This aims to reduce the futile surgery rate.…”
Section: The Imaging Pathway At Stagingmentioning
confidence: 99%
“…The combined use of PET and CT scanning is expected to offer a single test to identify possible metastases and determine if they are metabolically active. This technique has shown significant promise in esophageal cancer (Walker et al 2011). However, to date, PET-CT has not been evaluated in gastric cancer staging, particularly in conjunction with EUS.…”
mentioning
confidence: 99%
“…The clinical significance of falsenegative nodal assessment is, however, expected to be less when these nodes are in a peritumoral location because such nodes are likely to be resected with the primary tumor or included in the radiation treatment volume. Although some studies have also revealed a moderate rate of falsenegative nodes on PET/CT (17,26), this is to be expected when any imaging modality is compared with detailed histologic evaluation, which can detect even microscopic nodal deposits. CSI has similar limitations.…”
Section: Discussionmentioning
confidence: 99%